2019
DOI: 10.3390/ijerph16071280
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Effects of Water Immersion on Health Outcomes: An Integrative Review

Abstract: Hydrotherapy is widely used for the treatment and rehabilitation of patients, but it can also be applied to prevent diseases in healthy people. This review investigates the health effects of water immersion, a form of hydrotherapy, and the mechanisms by which the properties of water elicit such an effect. We searched PubMed, EMBASE, Cochrane Library, and CINAHL to identify relevant articles, of which 13 met the inclusion criteria. Various factors of water immersion were investigated in the 13 selected articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 43 publications
0
37
0
5
Order By: Relevance
“…The differences found between both experiments could be explained by the temperature used (4 • C vs. 10 • C) but also by the duration of the immersion (short intermittent immersions versus a continuous 20-min immersion). We decided to choose 10 • C and 42 • C respectively for 20-min based on the available literature which suggested temperatures ranging between 10-15 • C for CWI and >36 • C for WWI with applications lasting at least 10 min to yield results [4,6,8,31]. However, a systematic review published shortly afterward concluded that 11-15 min of CWI is considered to provide the best results; therefore, future research should take this timeframe as optimal [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences found between both experiments could be explained by the temperature used (4 • C vs. 10 • C) but also by the duration of the immersion (short intermittent immersions versus a continuous 20-min immersion). We decided to choose 10 • C and 42 • C respectively for 20-min based on the available literature which suggested temperatures ranging between 10-15 • C for CWI and >36 • C for WWI with applications lasting at least 10 min to yield results [4,6,8,31]. However, a systematic review published shortly afterward concluded that 11-15 min of CWI is considered to provide the best results; therefore, future research should take this timeframe as optimal [31].…”
Section: Discussionmentioning
confidence: 99%
“…The search for the optimal physical condition and the monitoring of physiological parameters in athletes have always been topics of study for researchers, trainers and coaches [1,2]. Water immersion has been used in both sports and rehabilitation for several decades and its effects on several physiological parameters, including inflammatory and metabolic markers, blood flow and nerve transmission are well-documented in the literature [3][4][5][6][7][8]. The effects of water immersion appear as thermal, mechanical and chemical effects, either alone or as mixed effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is no conclusive evidence 2 to support that a particular type of hydrotherapy accelerates wound healing, healing of stretched skeletal muscle and reduces pain at operative There is no definitive protocol or guidelines reported with evidence about the type of hydrotherapy with required temperature, its duration and frequency of body part immersion. 3,4 There are no publication suggesting the usage of any specific antiseptic solution speeds up the process of wound healing. There is no documentary evidence stating the practice of any particular type of seitz bath accelerates the wound healing and its effectiveness in the pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from water-based studies indicates regular deep or shallow water exercise can exert beneficial effects on cardiorespiratory fitness, strength, and body fat distribution [ 10 ]. Cardiovascular function improvement can be explained by the elevation in cardiac output due to the blood flow shift to the main blood vessels while immersed [ 19 ]. The hydrodynamic properties of water offer safety, facilitating training and testing for individuals with compromised musculoskeletal, neurologic, and cardiorespiratory conditions [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%